2020
DOI: 10.3390/s20144014
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Varroosis Based on Bee Brood Samples Testing with Use of Semiconductor Gas Sensors

Abstract: Varroosis is a dangerous and difficult to diagnose disease decimating bee colonies. The studies conducted sought answers on whether the electronic nose could become an effective tool for the efficient detection of this disease by examining sealed brood samples. The prototype of a multi-sensor recorder of gaseous sensor signals with a matrix of six semiconductor gas sensors TGS 823, TGS 826, TGS 832, TGS 2600, TGS 2602, and TGS 2603 from FIGARO was tested in this area. There were 42 objects belonging to 3 class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The Figaro 6-sensor TGS device we used has so far given satisfactory results in Varroa diagnostics, both in the laboratory (ref. [ 12 ] and in the field conditions [ 11 ]. We also successfully detected colonies on MYPGP media P.l.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Figaro 6-sensor TGS device we used has so far given satisfactory results in Varroa diagnostics, both in the laboratory (ref. [ 12 ] and in the field conditions [ 11 ]. We also successfully detected colonies on MYPGP media P.l.…”
Section: Discussionmentioning
confidence: 99%
“…These devices have found applications in the diagnosis of diseases in plants [ 8 ], animals [ 9 ], and humans [ 10 ]. In the case of bee diseases, an array of six solid-state gas sensors can distinguish bee colonies heavily infected with the Varroa destructor parasite from healthy colonies [ 11 ] and can diagnose Varroa by examining brood samples infected with this mite [ 12 ]. The effectiveness in detecting American foulbrood in bee colonies by the multi-sensor device in preliminary studies was confirmed by a team of scientists from Australia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements to reduce the number of hive visitations and negative impacts upon the colonies can be only be a positive step. Currently, the use of gas sensors (otherwise known as electronic noses, capable of identifying complex odours (Bąk et al 2020)) and video for detecting mite presence in hives are being explored. At present, these sensors are being tested for their ability to discriminate between healthy and mite-infested colony odours (Bąk et al 2020;Szczurek et al 2020a;Szczurek et al 2020b;Konig 2021), and in most cases these can be inserted into a hive and left to carry out continuous measurements that can be accessed remotely (Szczurek et al 2020a;Szczurek et al 2020b;Konig 2021).…”
Section: Remote Varroa Monitoring Techniquesmentioning
confidence: 99%
“…Table 1. The characteristics of semiconductor gas sensors, which were used in the multi-sensor array ( [9], https://www. figaro.co.jp/en (accessed on 17 July 2021)).…”
Section: Construction and Mechanism Of The Mca-8 Device's Operationmentioning
confidence: 99%
“…The most dangerous disease that plagues the honey bee is varroosis. It was shown that a matrix of six semiconductor gas sensors can distinguish bee colonies heavily infected with Varroa destructor from healthy ones [8], and this allows for the diagnosis of varroosis based on the examination of brood samples infected with this mite [9]. Another dangerous disease of bees is American foulbrood (AFB), caused by the Paenibacillus larvae larvae L. bacterium.…”
Section: Introductionmentioning
confidence: 99%